An Analysis of English Learning System at Ar-Risalah Islamic Modern Boarding School Lubuklinggau - Muhammad Ade Rizky Ade; Ayu Oktaviani; Yulfi (CV Grasta Glory, 2026)
This study aimed to analyze the English Learning System at Ar-Risalah Islamic Modern Boarding School Lubuklinggau. This research used descriptive qualitative Method with participants who amounted to 3 groups of data sources namely students, English teacher and coordinator curriculum. Then, the technique in collecting data in this study used instrument triangulation namely, questionnaires and interviews based on Masters’s theory (2023). Furthermore, for data analysis this study used a questionnaire to calculate the percentage per indicator while interviews were analyzed qualitatively. The results show that the English curriculum implemented is relevant and beneficial for students. The assessment process runs well with various forms of evaluation, although it still needs strengthening on the aspect of student participation. The teaching done by teachers is considered effective because it uses varied methods that are tailored to the needs of students. Support for students also runs through additional guidance and adequate supporting facilities. School leadership plays an active role in improving the quality of learning through supervising and coaching teachers, although direct involvement in the classroom is still limited. In addition, the learning ecosystem at school is supportive, as seen from the collaboration with parents, communities, and the provision of innovation spaces and learning activities outside the classroom that support students' real-life experiences.